Estrutura da população e período reprodutivo de Leporinus piau Fowler, 1941(Characiformes: Anostomidae) no reservatório de pau dos ferros, semiárido brasileiro - Araújo, Darlan Dantas Alves de (Universidade Federal Rural do Semi-Árido, 2015)
In the brazilian northeast due to seasonality of rivers and modest hydrological network, water security policy was established, based on the accumulation of water during the rainy season, through the reservoirs construction. This process generate human benefits, but also ecological consequences such as loss of aquatic biodiversity, change in the connectivity of water bodies and modification of biological processes such as reproduction and recruitment of species. In Apodi/Mossoró River basin , Leporinus piau Fowler,1941 is quite important for artisanal and subsistence fishing, however it is necessary to better understand their biology, to establish more effective conservation and management measures. In this context, the objective this work was to study the population structure and reproductive dynamics of Leporinus piau (Fowler, 1941), in the reservoir of Pau dos Ferros, Brazilian semiarid. Specimens were collected quarterly from February 2011 to November 2012 using gillnets. The specimens captured were counted and measured the standard length (cm), total weight (g), and dissected to identify sex, and gonadal maturity stage and weight of gonads (g). Were captured 555 individuals. The highest CPUE value was registered in May/2011 (0.0259 ind. m2*h) and lowest was in August/2012 (0.0008 ind. m2*h). The standard length ranged between 5.9 and 20.7cm and total weigh between 4.16 and 271.50g. The length class of 10-15cm was the most frequent of individuals captured for both sexes. The species presented isometric growth (b=3.01) and L50 was estimated to be 12.76cm. Of individuals captured, 276 were juveniles, 180 males and 99 females. The highest GSI value was observed in February/2011 for females (10.69) and males (5.72). There was a significant a positive correlation between GSI and rainfall. We conclude that the population of L. piau is established in the reservoir with some alterations its population attributes and reproductive period was determined between February and May
Population structure and reproductive dynamic of leporinus piau Fowler (Characiformes: Anostomidae) in the Pau dos Ferros reservoir, Brazilian semiarid
Keywords: Ecology - biodiversity; Migratory Fish; Stocks; Fish populations; Pau dos Ferros / RN - Reservoir; weir; Ecologia - biodiversidade; Peixes migradores; Ictiofauna; Pau dos Ferros/RN - Reservatório; Açude; CIENCIAS AGRARIAS::MEDICINA VETERINARIA